Associations Between Genetic Variants in MCT2 (rs3763980, rs995343, rs3763979) and MCT4 (rs11323780) with Blood Lactate Kinetics Before and After Supramaximal Exercise - Maculewicz, Ewelina; Bojarczuk, Aleksandra; Mastalerz, Andrzej; Johne, Monika; Mróz, Anna; Garbacz, Aleksandra; Stastny, Petr (International journal of molecular sciences, 2025)
Despite progress in understanding the role of monocarboxylate transporters (MCTs) in lactate (LA) accumulation and removal, it remains unclear whether MCT2 and MCT4 variants enhance LA utilization. This study assessed associations between MCT2 (rs3763980, rs995343, rs3763979) and MCT4 (rs11323780) polymorphisms and LA concentration. A total of 337 male athletes from the Czech Republic and Poland, divided into elite, sub-elite, and physically active individuals, completed two all-out Wingate tests. Before these tests, DNA was collected and analyzed for single-nucleotide polymorphisms (SNPs). LA concentrations were measured before and after the tests. MCT2 rs995343 showed the broadest associations. It was significantly associated with resting LA (LArest) in the overall cohort (codominant: false discovery rate (FDR)-adjusted p = 0.04; dominant: FDR-adjusted p = 0.03) and with peak LA concentration (LAmax), accumulation (ACC), and clearance (DCC) in the physically active group (all models: FDR-adjusted p = 0.02-0.04). MCT2 rs3763980 was associated with LArest in the overall group (codominant and recessive: FDR-adjusted p = 0.04). MCT2 rs3763979 was associated with LArest (FDR-adjusted p = 0.009-0.003) and LA30' (FDR-adjusted p = 0.003-0.04) in the overall and physically active cohorts. MCT4 rs11323780 was associated with LArest in elite athletes (recessive: FDR-adjusted p = 0.03) and with ACC in the physically active group (codominant and recessive: FDR-adjusted p = 0.03). These findings indicate that MCT polymorphisms contribute to variability in LA metabolism, influencing anaerobic performance and recovery.
Keywords: Young Adult; Muscle Proteins; Lactic Acid; Monocarboxylic Acid Transporters; Male; physical activity; mladý dospělý; genotype; Athletes; svalové proteiny; sportovci; genetic variants; Adult; lactate kinetics; dospělí; mužské pohlaví; jednonukleotidový polymorfismus; Exercise; elite athletes; sub-elite athletes; přenašeče monokarboxylových kyselin; sprint; kyselina mléčná; kinetika; Polymorphism, Single Nucleotide; lidé; Symporters; Humans; symportéry; athletic training; cvičení; Kinetics